1997
DOI: 10.1117/12.275739
|View full text |Cite
|
Sign up to set email alerts
|

<title>Measurement of transverse strains with fiber Bragg gratings</title>

Abstract: In this paper, we present a method to measure two components of transverse strain in an optical fiber using a single Bragg grating written into high-birefringent, polarization-maintaining (PM) fiber. The reflected spectrum from this grating contains two peaks corresponding to the two orthogonal polarization modes of the fiber. If the axial strain and temperature in the fiber is known, then two components of transverse strain can be computed from the changes in wavelength of the two peaks. A Bragg grating writt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 14 publications
0
43
0
Order By: Relevance
“…In this case, two planepolarized waves propagate in the fiber core, with the principal directions of polarization oriented parallel to the directions of the principal strains. The wavelength changes for each axis are explicitly given by [22][23][24] 2…”
Section: Fbg Sensing Principlesmentioning
confidence: 99%
“…In this case, two planepolarized waves propagate in the fiber core, with the principal directions of polarization oriented parallel to the directions of the principal strains. The wavelength changes for each axis are explicitly given by [22][23][24] 2…”
Section: Fbg Sensing Principlesmentioning
confidence: 99%
“…To avoid ambiguity due to coatings bare fiber gratings were used for these tests. The results of these tests showed transverse strain sensitivity of about 30 microstrain for a 0.01 nm resolution demodulator [6].…”
Section: Performance and Test Resultsmentioning
confidence: 97%
“…This information which is contained in the spreading of the profiles of the fiber grating is a new tool that could be ofconsiderable value for understanding manufacturing processes. (6) Geometries other than circular of polarization preserving fiber need to be studied. Varying the geometry by implementing 3 axis fiber grating sensors into polarization preserving fibers that are D shaped (such as those pioneered by Dyott of Andrew Corporations) or flattened on both sides (developed by Roger Stolen at Bell Labs) have two potential advantages.…”
Section: Summary and Evaluationmentioning
confidence: 99%
“…However, the past studies have shown that the characteristics of a FBG under transverse load are quite different from axial load [7][8][9][10][11]. In the case of transverse load, the stress distribution along the two perpendicular directions across the cross-section of the fiber is different, which causes that the propagation constants of the two polarization modes x HE 11 and y HE 11 to be different.…”
Section: Introductionmentioning
confidence: 98%